May-Thurner syndrome causing venous thromboembolism in a young female with Sturge weber syndrome and connective tissue disease - Narula, Shubhank; Agarwal, Pankaj Kumar; Garg, Ambuj (International Journal of Research in Medical Sciences, 2023)
May-Thurner syndrome (MTS) is a rare condition characterized by the compression of the left common iliac vein by the overlying right common iliac artery. It is a unique causal reason for development of deep venous thrombosis (DVT) and pulmonary embolism (PE). Young females developing DVT should be examined and investigated with details as triggers can include trauma, pregnancy, autoimmunity. In this case report we report a case of a young female who had Sturge Weber Syndrome, and how a left hip pain was diagnosed as DVT which led to diagnosis of an underlying MTS and autoimmune trigger for her hypercoagulable state.